Whole-Body Prolyl Hydroxylase Domain (PHD) 3 Deficiency Increased Plasma Lipids and Hematocrit Without Impacting Plaque Size in Low-Density Lipoprotein Receptor Knockout Mice - Demandt, Jasper A. F.; van Kuijk, Kim; Theelen, Thomas L.; Marsch, Elke; Heffron, Sean P.; Fisher, Edward A.; Carmeliet, Peter; Biessen, Erik A. L.; Sluimer, Judith C. (Frontiers in Cell and Developmental Biology, 2021)
Background&aims Atherosclerosis as an important cause of clinical cardiovascular events. Atherosclerotic plaques are hypoxic, and reoxygenation improves plaque phenotype. Central players in hypoxia are hypoxia inducible factors (HIF) and their regulators, HIF-prolyl hydroxylase (PHD) isoforms 1, 2 and 3. PHD inhibitors, targeting all three isoforms, are used to alleviated anemia in chronic kidney disease. Likewise, whole body PHD1 and PHD2ko ameliorate hypercholesterolemia and atherogenesis. As the effect of whole body PHD3 is unknown, we investigated effects of germline whole-body PHD3ko on atherosclerosis. Approach & Results To initiate hypercholesterolemia, and atherosclerosis low-density lipoprotein receptor knockout (LDLrko) and PHD3/LDLr double knockout (PHD3dko) mice were fed a high cholesterol diet. Atherosclerosis and hypoxia marker pimonidazole were analyzed in aortic roots and brachiocephalic arteries. In contrast to earlier reports on PHD1 and PHD2 deficient mice, a small elevation in body weight, as well as increased plasma cholesterol and triglyceride levels were observed after 10 weeks of diet. Dyslipidemia might be explained by an increase in hepatic mRNA expression of Cyp7a1 and fatty acid synthase, while lipid efflux of PHD3dko macrophages was comparable to controls. Despite dyslipidemia, plaque size, hypoxia and phenotype were not altered in the aortic root, or in the brachiocephalic artery of PHD3dko mice. Additionally, PHD3dko mice showed enhanced blood hematocrit levels, but no changes in circulating, splenic or lymphoid immune cell subsets. Conclusion Here, we report that whole body PHD3dko instigated an unfavorable lipid profile and increased hematocrit, in contrast to other PHD isoforms, yet without altering atherosclerotic plaque development.